Analysis of the use of Slang Language in Usage Indonesian Language Among Students of Vocational High School - Yayu Agustiani; Wikanengsih; Ika Mustika (JLER (Journal of Language Education Research), 2023)
Language is a tool used by humans to interact with each other. With human language, humans can interact anytime and anywhere according to their respective regional languages, especially Indonesian. Indonesian is the unifying language of the nation and must be upheld by its citizens. But in reality, there are still many citizens who experience obstacles in interacting due to a lack of language skills. Errors in language can happen to anyone, be it children, adults, or seniors; it depends on the person's understanding of the language according to the rules. This study aims to analyze the impact of using slang that often occurs among schoolchildren at SMK Miftahul Ihsan. This study uses a qualitative descriptive method that describes data on language errors that are often used by schoolchildren. The facts about the language errors were obtained by using the recording and listening methods in class. Besides the data collection techniques, this study used a recording device to record all the conversations of the informants in the class. The results of the study indicate that the impact of using slang that occurs in schoolchildren or adolescents is inherent and used in students' daily lives so that it becomes a habit. The language errors are: 1) The occurrence of deviant errors or slang; 2) Errors in the use of joining suffixes; 3) Errors in omitting one letter (phoneme) in a sentence; and 4) the replacement of diphthongs "au" and "ai" with "o" and "e.".